JOB PERFORMANCE LEVEL OF THE REGULAR FACULTY EMPLOYEES FROM THE SELECTED COLLEGES OF MINDANAO STATE UNIVERSITY -MARAWI CITY - Marecon Viray; Ryan Rey B. Lumacad; Jalil G. Darimbang; Kim Syrus P. Patic; Roland R. Pritos (International Relations Study Program of Universitas Kristen Indonesia (UKI), 2022)
The study focused on determining the job performance level of the permanent employees in Mindanao State University -Marawi City. The data also showed that the respondents were knowledgeable enough on matters concerning to job performance. Statement indicators assessed whether a person performs his/her a job well -this is an important criterion for the organizational outcome and success because it is a measurement of an employee’s behavior despite the influences of stress, workload, work environment and strategy concerns. For their perception on job performance level in terms of salary, the findings imply that the respondents were satisfied of the university’s salary and the benefit packages. Although some uncertainty occurred when it comes to the “rewards” granted to them for the quality of their efforts. Overall, it implies that the permanent faculty members of the selected five (5) colleges of Mindanao State University -Marawi City, namely -College of Agriculture; College of Business Administration and Accountancy; College of Education; College of Natural Science and Mathematics; and College of Social Science and Humanities are satisfied and are happy with working in their respective colleges while it is evident from the responses that the proponents of this study received through the given indicators like salary, working environment, workload and etc. The researchers therefore conclude that the respondents have high level of job performance. Keywords: Job performance, permanent employees, salary, working environment, workload